Konsep Pendidikan Merdeka Belajar Perspektif Filsafat Progresivisme (The Emancipated Learning Concept of Education in Progressivism Philosophy Perspective) - Jems Sopacua; Muhammad Rijal Fadli (Potret Pemikiran, 2022)
This article aims to examine the concept of freedom of learning from the point of view of the progressivism philosophy of education. The method used is literature study with a hermeneutic approach to explaining the reality that occurs with elements of interpretation and description. The concept of freedom of learning education is under the modern progressivism educational philosophy and wants a fundamental change in the implementation of education to be better, better quality, and provide real benefits to students. Progressivism has emphasized the importance of the fundamentals of independence and freedom to students, by giving them the freedom to develop the competencies, interests, and talents they already have, without the obstacles of formal regulations which sometimes shackle their creativity and thinking power to be better. The concept of freedom of learning education in Indonesia which has become a new policy is considered to be able to change the existing education system. The harmony of independent learning with the philosophy of progressivism provides a new perspective on the orientation of education in Indonesia, in practice, it presents a natural learning space and allows children to grow and develop according to their interests and talents so that the goal of forming individuals with character can be realized.